Intertidal seaweeds from North Atlantic Patagonian coasts, Argentina - Croce, Maria Emilia (2015)
The coasts located between 39°S and 41°S in the Argentinean biogeographic province have been described by impoverished seaweed assemblages, however the floristic information about this region is sparse. The aim of this study was to survey the intertidal seaweeds inhabiting three sites in the oceanographic system “El Rincon” (Buenos Aires, Argentina). A total of 42 taxa were identified with a dominance of Rhodophyta species. The sandstone outcrops (SO) had 29 taxa, whereas both the tidal flat (TF) and oyster reefs (OR) had 11 taxa. The estuarial species Ulva intestinalis and Ulva prolifera were recorded in TF, whereas calcified macroalgae were only found in SO. The differences in richness and composition of seaweed assemblages were associated with substrate type, wave exposure, incident light and salinity. These differences were also evidenced by a dissimilar number of functional groups, which was higher in SO with a dominance of filamentous macroalgae.